Histopathologic and physiologic effect of bifurcation stenting: current status and future prospects. (3rd March 2020) - Cornelissen, Anne; Guo, Liang; Sakamoto, Atsushi; Jinnouchi, Hiroyuki; Sato, Yu; Kuntz, Salome; Kawakami, Rika; Mori, Masayuki; Fernandez, Raquel; Fuller, Daniela; Gadhoke, Neel; Kolodgie, Frank D.; et al.
ABSTRACT: Introduction : Coronary bifurcation lesions are involved in up to 20% of all percutaneous coronary interventions (PCI). However, bifurcation lesion intervention is associated with a high complication rate, and optimal treatment of coronary bifurcation is an ongoing debate. Areas covered : Both different stenting techniques and a variety of devices have been suggested for bifurcation treatment, including the use of conventional coronary stents, bioresorbable vascular scaffolds (BVS), drug-eluting balloons (DEB), and stents dedicated to bifurcations. This review will summarize different therapeutic approaches with their advantages and shortcomings, with special emphasis on histopathologic and physiologic effects of each treatment strategy. Expert opinion : Histopathology and clinical data have shown that a more simple treatment strategy is beneficial in bifurcation lesions, achieving superior results. Bifurcation interventions through balloon angioplasty or placement of stents can importantly alter the bifurcation's geometry and accordingly modify local flow conditions. Computational fluid dynamics (CFD) studies have shown that the outcome of bifurcation interventions is governed by local hemodynamic shear conditions. Minimizing detrimental flow conditions as much as possible should be the ultimate strategy to achieve long-term success of bifurcation interventions.